Joseph Baker & Nick Wattie - new insights into the concept of innate talent in sport - Lisa Steidl-Müller (Ed.) (Bern Open Publishing, 2019)
In this target article, Joseph Baker and Nick Wattie revisited the review article on the evidence for innate talent published by Howe, Davidson and Sloboda 20 years ago, and focused mainly on whether this concept was reasonable and scientifically sound, and whether the concept of innate talent was valid also in the world of sport. The main article (CISS_3:006) is then discussed by five peer commentaries (CISS_4:102 - CISS_4:106), written by research experts in this field. Finally, Joseph Baker and Nick Wattie provided a closing response (CISS_4:108) acknowledging critiques, suggestions, and extensions brought forward by the commentators.